2009
DOI: 10.1063/1.3089379
|View full text |Cite
|
Sign up to set email alerts
|

Flexible low voltage nonvolatile memory transistors with pentacene channel and ferroelectric polymer

Abstract: We report on the fabrication of pentacene-based nonvolatile memory thin-film transistors (NVM-TFTs) with thin poly(vinylidene fluoride/trifluoroethylene) ferroelectric gate insulators. Our NVM-TFT adopts flexible polyethersulfone substrate and operates under the low voltage write-erase (WR-ER) pulses of ±13∼±20 V with field effect mobilities of 0.1–0.18 cm2/V s, depending on the ferroelectric polymer thickness. Our NVM-TFT displays good memory window (ΔV) of 2.5–8 V and also exhibits WR-ER current ratio of 20–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
61
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 12 publications
2
61
0
Order By: Relevance
“…Ferroelectric transistors can also be fabricated using P(VDF-TrFE) for each bit in FeRAM [Naber et al, 2005;Lee et al, 2009], however, the reliability still needs to be improved for future applications.…”
mentioning
confidence: 99%
“…Ferroelectric transistors can also be fabricated using P(VDF-TrFE) for each bit in FeRAM [Naber et al, 2005;Lee et al, 2009], however, the reliability still needs to be improved for future applications.…”
mentioning
confidence: 99%
“…18,19 It has been reported that TOMDs have memory functions from ferroelectric polymers, metal nanoparticles or charge trapping layers, and polymer energy well structures. [20][21][22][23][24][25][26][27][28][29][30] However, most TOMDs reported to date have limitations with respect to high operation voltages and/or poor retention (stability) characteristics, even though basic memory functions in transistor structures can be welldemonstrated. Thus, it is very important to achieve both low voltage and high retention characteristics at the same time for further consideration toward commercialization of TOMDs, particularly for mobile applications, of which the first priority is low power consumption, as well as stability.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless organic semiconductors can be formed at low temperatures, and most of them can be deposited by a solution process. Thus, many researchers used organic semiconductors when they fabricated FeFETs on flexible substrates [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%